A two-component organic silicone adhesive for heat conduction of power battery structure
By adding modified micro-nano high thermal conductivity mixed powder and modified silicon carbide whiskers into the two-component silicone adhesive for thermal conductivity of power battery structures, and using liquid reactive flame retardants, tackifiers and cross-linking agents, The problem of low thermal conductivity and unsatisfactory flame retardancy in the existing technology is solved, and an adhesive with high thermal conductivity and excellent flame retardant properties is realized.
Patent Information
- Application Number
- CN202411452723.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The silicone adhesives used for thermal conductivity in existing power battery structures have problems such as low thermal conductivity, poor fluidity, poor bonding strength, insufficient compression resistance and unsatisfactory flame retardancy, which is difficult to meet the safety and long-life use needs of power batteries.
Using a two-component silicone adhesive, by adding modified micro-nano high thermal conductivity mixed powder and modified silicon carbide whiskers to component A, and adding liquid reactive flame retardants, tackifiers and Cross-linking agent ensures uniform dispersion and efficient cross-linking of thermally conductive fillers, and improves the thermal conductivity and mechanical properties of the colloid.
It achieves high thermal conductivity (6.29~6.76W/(m·k)), high fluidity, high bonding strength and high compressive strength. It also has excellent flame retardant properties, significantly improving the thermal conductivity and performance of the power battery structure. Security.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a two-component organic silicone adhesive for heat conduction of a power battery structure, belonging to the technical field of adhesives. Background Art
[0002] Thermally conductive flame retardant potting glue is often used in the fields of new energy start-stop batteries and their modules, electronic components and drive power supplies. At present, the commonly used room temperature curing thermally conductive flame retardant potting glues are: silicone thermally conductive flame retardant potting silica gel, epoxy thermally conductive flame retardant potting glue, and polyurethane thermally conductive flame retardant potting glue. Among them, epoxy thermally conductive flame retardant potting glue and polyurethane thermally conductive flame retardant potting glue have high bonding strength, high hardness and good potting effect, but when the battery and its module, electronic components and drive power supply inside the potting fail, it is difficult to disassemble, and other fault-free devices are easily damaged during the disassembly process, which is not conducive to maintenance; moreover, epoxy thermally conductive flame retardant potting glue and polyurethane thermally conductive flame retardant potting glue have almost no elasticity and poor shock absorption effect. When encountering collision or severe vibration, it is easy to cause the start-stop battery, electronic components and drive power supply to burn or be damaged, leading to accidents and seriously shortening the service life. At present, the organic silicone thermal conductive flame retardant potting silica gel on the market basically uses a side chain hydrogen-containing crosslinking agent, and the resulting potting glue has imperfect performance, unsatisfactory thermal conductivity, low bonding strength, low compression modulus, and cannot resist external stress impact and extrusion, and cannot protect the device, causing damage to the device. In addition, most of the organic silicone thermal conductive flame retardant potting silica gels on the market have high viscosity, which is not conducive to processing and has poor process applicability.
[0003] Chinese patent CN 112940674A discloses a high temperature resistant flame retardant silicone potting compound with good high temperature stability and flame retardant properties. However, the use of a side chain hydrogen-containing crosslinking agent results in a high hardness and low compression modulus of the potting compound product, which cannot solve the technical problems of difficult disassembly and repair and poor shock absorption effect. In addition, the thermal conductivity is not particularly ideal.
[0004] Chinese patent CN106867444A discloses a low-density flame-retardant thermally conductive potting glue for automotive power batteries and its preparation method, which is prepared from component A and component B, wherein component A is composed of base material, hydrogen-containing silicone oil crosslinking agent, curing inhibitor and vinyl polydimethylsiloxane; component B is composed of base material, platinum complex catalyst and vinyl polydimethylsiloxane; the base material is composed of vinyl polydimethylsiloxane, composite halogen-free flame retardant and hollow glass microspheres; the composite halogen-free flame retardant is composed of at least one nitrogen-containing flame retardant and at least one inorganic flame retardant, and the weight ratio of the nitrogen-containing flame retardant to the inorganic flame retardant is 0.3 to 3.5:1. Although the low-density flame-retardant thermally conductive potting glue obtained in this patent has good fluidity, its thermal conductivity is relatively low, and the maximum value can only reach 0.62W / (m·k).
[0005] From the above, we can see that the current organic silicone adhesives used for thermal conductivity of power battery structures still have outstanding problems such as low thermal conductivity, poor fluidity, poor bonding strength, insufficient compression resistance and unsatisfactory flame retardancy. Therefore, the development of organic silicone adhesives for thermal conductivity of power battery structures with high thermal conductivity, high fluidity, high bonding strength, high compressive strength and excellent flame retardancy is of great practical significance for the safe and long-life use of liquid lithium-ion batteries. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a two-component organic silicone adhesive for thermal conductivity of power battery structures to achieve the following invention objectives: to prepare a two-component organic silicone adhesive for thermal conductivity of power battery structures with high thermal conductivity, high fluidity, high bonding strength, high compressive strength and excellent flame retardant properties.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A two-component organic silicone adhesive for heat conduction of a power battery structure, the two-component organic silicone adhesive for heat conduction of a power battery structure consisting of component A and component B, and the components A and B are mixed evenly in a volume ratio of 5:3-5 before use during gluing;
[0009] The specific formula of the component A is, in parts by weight:
[0010] 110-160 parts of α,ω-dihydroxy polydimethylsiloxane,
[0011] 0.5~2.5 parts of fumed silica,
[0012] 70~100 parts of modified micro-nano high thermal conductivity mixed powder,
[0013] Modified silicon carbide whisker 6~18 parts,
[0014] 25-45 parts of liquid reactive flame retardant;
[0015] The particle size of the fumed silica is 10-100 nm;
[0016] The liquid reactive flame retardant is N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester;
[0017] The specific formula of the B component is, in parts by weight:
[0018] 10~25 parts of plasticizing liquid flame retardant,
[0019] Thickener 6~15 parts,
[0020] Catalyst 0.8~1.3 parts,
[0021] 3~6 parts of dewatering agent,
[0022] 8~15 parts of cross-linking agent,
[0023] 4-9 parts of auxiliary cross-linking agent;
[0024] The plasticizing liquid flame retardant is trioctyl phosphate;
[0025] The tackifier is liquid polycarbosilane;
[0026] The number average molecular weight of the liquid polycarbosilane is 600-900 g / mol, and the viscosity at room temperature is 200-400 mPa·s;
[0027] The catalyst is dibutyltin dilaurate;
[0028] The dewatering agent is vinyl trimethoxy silane;
[0029] The cross-linking agent is one of modified tannic acid and 4,4'-biphenylboronic acid;
[0030] The modified tannic acid has a preparation method comprising: dissolving tannic acid in acetone, then heating and maintaining the temperature at 50-70°C, controlling the stirring rate at 300-600 rpm, adding 3-isocyanate propyltrimethoxysilane under stirring, condensing and reflux, and then reacting at a constant temperature for 4-9 hours, continuing to maintain the constant temperature, performing vacuum distillation, and removing the acetone to obtain a solid powder, which is the modified tannic acid;
[0031] The mass ratio of the tannic acid, acetone and 3-isocyanatepropyltrimethoxysilane is 10-25:100-250:3-6;
[0032] The auxiliary cross-linking agent is diphenylsilanediol;
[0033] The following are further improvements to the above technical solution:
[0034] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0035] After placing the nano aluminum nitride powder and the carbonyl iron powder in a 100-130° C. oven and drying for 9-13 hours, the powder is cooled to room temperature in a dry environment, and then added to a high-speed dispersion kettle, followed by adding toluene and oleyl linoleate, and strongly dispersed at a speed of 8000-13000 rpm for 6-10 hours, and then reducing the dispersion rate to 4000-7000 rpm, adding silane substances, and heating and maintaining the temperature at 60-90° C., and reacting at the constant temperature for 4-8 hours, and then reducing the temperature to room temperature, centrifugally separating, and washing the separated solid with anhydrous ethanol for 3-5 times, and then drying it in a 50-80° C. vacuum drying oven for 6-10 hours to obtain a modified micro-nano high thermal conductivity mixed powder;
[0036] The particle size of the nano aluminum nitride powder is 10-100 nm;
[0037] The particle size of the carbonyl iron powder is 0.5-3 μm;
[0038] The silane substance is one of hexamethyldisilazane, hexaethyldisilazane, octamethylcyclotetrasilazane, tetramethyldisilazane, hexamethylcyclotrisilazane and hexamethyldisilazane;
[0039] The mass ratio of the nano aluminum nitride powder, carbonyl iron powder, toluene, oleyl linoleate, and silane substances is 10-20:30-55:160-240:3-10:5-10.
[0040] Step 2: Preparation of modified silicon carbide whiskers
[0041] After the silicon carbide whisker is placed in a 100-130°C oven and dried for 5-10 hours, it is cooled to room temperature in a dry environment and then added to a high-speed dispersion kettle, followed by adding toluene, and strongly dispersed at a speed of 6000-9000 rpm for 5-8 hours, the dispersion rate is reduced to 2000-5000 rpm, 3-aminopropyltrimethoxysilane is added, the temperature is raised and kept constant at 70-95°C, and after constant temperature reaction for 6-11 hours, the temperature is reduced to room temperature, filtered, and the filtered solid is washed with anhydrous ethanol for 2-4 times, and then placed in a 40-70°C vacuum drying oven for 4-8 hours to obtain a modified silicon carbide whisker;
[0042] The silicon carbide whisker has a diameter of 0.1-0.5 μm and a length of 10-30 μm;
[0043] The mass ratio of the silicon carbide whisker, toluene and 3-aminopropyltrimethoxysilane is 15-45:150-270:4-9.
[0044] Step 3: Preparation of component A
[0045] According to the specific formula of component A of the two-component organic silicone adhesive for power battery structure thermal conductivity in parts by weight, α, ω-dihydroxy polydimethylsiloxane, liquid reactive flame retardant and fumed silica are put into a double planetary mixer, evacuate and maintain the vacuum state in the mixer, control the stirring rate at 110-130 rpm and the dispersion rate at 8500-12000 rpm, continue to stir and disperse for 4-8 hours, then add the modified micro-nano high thermal conductivity mixed powder, continue to stir and disperse for 7-12 hours, maintain the stirring rate unchanged, reduce the dispersion rate to 3500-5000 rpm, then add the modified silicon carbide whisker, continue to stir and disperse for 8-11 hours, and obtain the adhesive solution. After vacuum degassing, fill it into a plastic finished product bottle, and seal it with nitrogen to obtain the finished product of component A.
[0046] Step 4: Preparation of component B
[0047] According to the specific formula of component B of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, the plasticizer liquid flame retardant, thickener, catalyst, dehydrating agent, cross-linking agent and auxiliary cross-linking agent are placed in a double planetary mixer, and the vacuum state in the mixer is evacuated and maintained. The stirring rate is controlled at 110-130 rpm and the dispersion rate is 8000-10000 rpm. After stirring and mixing for 6-10 hours, the adhesive solution is obtained. After vacuum degassing, it is filled into plastic finished product bottles, and sealed with nitrogen to obtain the finished product of component B.
[0048] Compared with the prior art, the present invention achieves the following beneficial effects:
[0049] 1. The nano-scale aluminum nitride powder, micron-scale carbonyl iron powder and micron-scale silicon carbide whiskers added in the present invention, wherein the nano-scale powder is densely filled in the gaps between the micron-scale powders. Due to the size complementarity effect, the micro-nano powders have very good contact with each other, which promotes the overall thermal conductivity of the thermal conductive filler inside the colloid. Furthermore, the highly thermally conductive silicon carbide whiskers can cooperate with the above two micro-nano powders to form a continuous thermal conductive network, which avoids the state of local disconnection of the thermal conductive network caused by uneven powder dispersion or local agglomeration as much as possible, so that the thermal conductivity of the colloid can be improved to the greatest extent, and a silicone structural adhesive with excellent thermal conductivity can be obtained;
[0050] 2. The present invention uses silane substances with very high hydroxyl reactivity and particularly strong hydrophobicity to modify the surface of nano aluminum nitride powder and carbonyl iron powder. The hydroxyl functional groups contained on the surface of these two powders will quickly react with the silane substances to form a highly hydrophobic surface, which ensures the uniformity of dispersion of the nano aluminum nitride powder and carbonyl iron powder in the silicone resin glue, thereby promoting the two powders to form an effective thermal conductive network inside the colloid. In addition, the present invention uses 3-aminopropyltrimethoxysilane to modify the surface of silicon carbide whiskers. Like the modification mechanism described above, 3-aminopropyltrimethoxysilane also It will greatly promote the uniformity of the dispersion of silicon carbide whiskers in the glue. In addition, after 3-aminopropyltrimethoxysilane reacts on the surface of silicon carbide whiskers, amino groups will remain. There are lone pairs of electrons on the nitrogen atoms contained in the amino groups, which have very strong negative adsorption effects. Therefore, during the curing process of the colloid, due to volume shrinkage, the distance between the nano-aluminum nitride powder and the carbonyl iron powder and the modified silicon carbide whiskers is shortened. The surface of the modified silicon carbide whiskers is very easy to adsorb nano-aluminum nitride powder and carbonyl iron powder, so that it is easy to form a close contact between the micro-nano powder and the whiskers with a large aspect ratio. The thermal conductive network with good contact formed in this way will have a very good thermal conductive effect.
[0051] 3. The crosslinking agent added in the present invention is modified tannic acid and 4,4'-biphenylboronic acid. The tannic acid modified by 3-isocyanate propyltrimethoxysilane has a large number of trimethoxysilane functional groups at the end and has a very high reaction functionality. The 4,4'-biphenylboronic acid has four active hydroxyl groups at the end and is a tetrafunctional crosslinking agent. After these two substances are added to the colloid, they can provide very high crosslinking reaction activity and very high crosslinking degree during the curing process, which makes the density of the colloid after curing very high, thereby improving the mechanical properties of the colloid. In addition, after the density of the colloid is improved, the distance between the thermal conductive filler powder particles will be shortened, which will also increase the thermal conductivity of the colloid to a certain extent.
[0052] 4. The liquid reactive flame retardant added in the present invention, N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester, can not only reduce the viscosity of the glue solution and promote the dispersion effect of the thermal conductive filler, so that the glue solution has better fluidity to facilitate the sizing operation, but also can undergo a cross-linking reaction with the silicone resin to improve the mechanical properties of the colloid, and can also give the colloid very high flame retardant properties;
[0053] 5. The tackifier added in the present invention, i.e., liquid polycarbosilane, has very excellent bonding properties and can greatly improve the bonding properties of the adhesive to the substrate surface during the curing process of the adhesive. This is mainly because polycarbosilane contains Si-H bonds with relatively strong bonding force, and the hydrolysis reaction of Si-H bonds is also relatively active. After contacting with the substrate, the trace amount of moisture on the surface of the substrate enables the liquid polycarbosilane to quickly wet and adhere to the substrate and produce a hydrolysis and adhesion effect. Moreover, after the adhesive layer is cured, the liquid polycarbosilane will slowly undergo a porcelain cross-linking reaction in a high temperature environment, which will further increase the density of the adhesive layer after curing, maintain the dense bonding degree of the thermal conductive network, and further improve the high thermal conductivity of the thermal conductive network.
[0054] 6. The two-component organic silicone adhesive for heat conduction of power battery structure obtained by the present invention has a thermal conductivity of 6.29~6.76W / (m·k), a viscosity of the adhesive of 47870~51054mPa·s, a bonding strength of 4.17~4.82MPa, a tensile strength of 5.05~5.73MPa, a compression modulus of 11.9~13.5MPa, and a flame retardant grade of V0. DETAILED DESCRIPTION
[0055] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0056] Example 1: A two-component organic silicone adhesive for heat conduction of power battery structure
[0057] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0058] After drying the nano aluminum nitride powder and carbonyl iron powder in an oven at 120° C. for 12 hours, the powder was cooled to room temperature in a dry environment and then added to a high-speed dispersion kettle, followed by adding toluene and oleyl linoleate. After intensive dispersion at 11,000 rpm for 7 hours, the dispersion rate was reduced to 5,500 rpm, silane substances were added, the temperature was raised and kept constant at 80° C., and after 7 hours of constant temperature reaction, the temperature was reduced to room temperature and centrifuged. The separated solid was washed with anhydrous ethanol for 4 times and dried in a vacuum drying oven at 60° C. for 9 hours to obtain a modified micro-nano high thermal conductivity mixed powder.
[0059] The particle size of the nano aluminum nitride powder is 40 nm;
[0060] The particle size of the carbonyl iron powder is 1 μm;
[0061] The silane substance is hexamethyldisilazane;
[0062] The mass ratio of the nano aluminum nitride powder, carbonyl iron powder, toluene, oleyl linoleate, and silane substances is 16:40:180:7:8.
[0063] Step 2: Preparation of modified silicon carbide whiskers
[0064] The silicon carbide whisker was placed in a 120°C oven for drying for 8 hours, cooled to room temperature in a dry environment, and then added to a high-speed dispersion kettle, followed by adding toluene, and dispersed vigorously at 7000 rpm for 6 hours, then the dispersion rate was reduced to 2800 rpm, 3-aminopropyltrimethoxysilane was added, and the temperature was raised and kept constant at 80°C. After constant temperature reaction for 9 hours, the temperature was reduced to room temperature, filtered, and the filtered solid was washed with anhydrous ethanol for 3 times, and then placed in a 65°C vacuum drying oven for drying for 5 hours to obtain modified silicon carbide whiskers;
[0065] The silicon carbide whisker has a diameter of 0.2 μm and a length of 22 μm;
[0066] The mass ratio of the silicon carbide whisker, toluene and 3-aminopropyltrimethoxysilane is 25:180:7.
[0067] Step 3: Preparation of component A
[0068] The specific formula of the component A is, in parts by weight:
[0069] 130 parts of α,ω-dihydroxy polydimethylsiloxane,
[0070] 1 part of fumed silica,
[0071] 80 parts of modified micro-nano high thermal conductivity mixed powder,
[0072] Modified silicon carbide whisker 11 parts,
[0073] 35 parts of liquid reactive flame retardant;
[0074] The particle size of the fumed silica is 70 nm;
[0075] The liquid reactive flame retardant is N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester;
[0076] According to the specific formula of component A of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, α, ω-dihydroxy polydimethylsiloxane, liquid reactive flame retardant and fumed silica are put into a double planetary mixer, evacuate and maintain the vacuum state in the mixer, control the stirring rate at 120 rpm and the dispersion rate at 11000 rpm, continue stirring and dispersing for 7 hours, then add the modified micro-nano high thermal conductivity mixed powder, continue stirring and dispersing for 10 hours, maintain the stirring rate unchanged, reduce the dispersion rate to 4000 rpm, then add the modified silicon carbide whisker, continue stirring and dispersing for 9 hours to obtain the glue solution, and then after vacuum degassing, fill it into plastic finished product bottles, fill it with nitrogen and seal it to obtain the finished product of component A.
[0077] Step 4: Preparation of component B
[0078] The specific formula of the B component is, in parts by weight:
[0079] 15 parts of plasticizing liquid flame retardant,
[0080] Thickener 9 parts,
[0081] 1 part of catalyst,
[0082] 5 parts of dewatering agent,
[0083] 11 parts of cross-linking agent,
[0084] 7 parts of auxiliary cross-linking agent;
[0085] The plasticizing liquid flame retardant is trioctyl phosphate;
[0086] The tackifier is liquid polycarbosilane;
[0087] The number average molecular weight of the liquid polycarbosilane is 700 g / mol, and the viscosity at room temperature is 320 mPa·s;
[0088] The catalyst is dibutyltin dilaurate;
[0089] The dewatering agent is vinyl trimethoxy silane;
[0090] The cross-linking agent is modified tannic acid;
[0091] The modified tannic acid is prepared by: dissolving tannic acid in acetone, then heating and maintaining the temperature at 65°C, controlling the stirring rate to 400 rpm, adding 3-isocyanate propyltrimethoxysilane under stirring, condensing and reflux, and then stirring and reacting at a constant temperature for 7 hours, and then continuing to maintain the constant temperature, vacuuming and distilling under reduced pressure, and after evacuating and removing the acetone, the obtained solid powder is the modified tannic acid;
[0092] The mass ratio of the tannic acid, acetone and 3-isocyanatepropyltrimethoxysilane is 15:190:5;
[0093] The auxiliary cross-linking agent is diphenylsilanediol;
[0094] According to the specific formula of component B of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, the plasticizer liquid flame retardant, thickener, catalyst, dehydrating agent, cross-linking agent and auxiliary cross-linking agent are placed in a double planetary mixer, and the vacuum state in the mixer is evacuated and maintained. The stirring rate is controlled at 125 rpm and the dispersion rate is 9500 rpm. After stirring and mixing for 9 hours, the adhesive solution is obtained. After vacuum degassing, it is filled into plastic finished product bottles, and sealed with nitrogen to obtain the finished product of component B.
[0095] Example 2: A two-component organic silicone adhesive for heat conduction of power battery structure
[0096] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0097] After the nano aluminum nitride powder and the carbonyl iron powder were placed in a 100° C. oven and dried for 9 hours, they were cooled to room temperature in a dry environment and then added to a high-speed dispersion kettle, followed by the addition of toluene and oleyl linoleate, and after intensive dispersion at 8000 rpm for 6 hours, the dispersion rate was reduced to 4000 rpm, silane substances were added, the temperature was raised and kept constant at 60° C., and after the constant temperature reaction for 4 hours, the temperature was reduced to room temperature and centrifuged, the separated solid was washed with anhydrous ethanol for 3 times, and then placed in a 50° C. vacuum drying oven and dried for 6 hours to obtain a modified micro-nano high thermal conductivity mixed powder;
[0098] The particle size of the nano aluminum nitride powder is 10 nm;
[0099] The particle size of the carbonyl iron powder is 0.5 μm;
[0100] The silane substance is hexaethyldisilazane;
[0101] The mass ratio of the nano aluminum nitride powder, carbonyl iron powder, toluene, oleyl linoleate, and silane substances is 10:30:160:3:5.
[0102] Step 2: Preparation of modified silicon carbide whiskers
[0103] After the silicon carbide whisker is placed in a 100°C oven and dried for 5 hours, it is cooled to room temperature in a dry environment and then added to a high-speed dispersion kettle, followed by adding toluene, and strongly dispersed at a speed of 6000 rpm for 5 hours, the dispersion rate is reduced to 2000 rpm, 3-aminopropyltrimethoxysilane is added, the temperature is raised and kept constant at 70°C, and after constant temperature reaction for 6 hours, the temperature is reduced to room temperature and filtered, and the filtered solid is washed twice with anhydrous ethanol, and then placed in a 40°C vacuum drying oven and dried for 4 hours to obtain a modified silicon carbide whisker;
[0104] The silicon carbide whisker has a diameter of 0.1 μm and a length of 10 μm;
[0105] The mass ratio of the silicon carbide whisker, toluene and 3-aminopropyltrimethoxysilane is 15:150:4.
[0106] Step 3: Preparation of component A
[0107] The specific formula of the component A is, in parts by weight:
[0108] 110 parts of α,ω-dihydroxy polydimethylsiloxane,
[0109] 0.5 parts of fumed silica,
[0110] 70 parts of modified micro-nano high thermal conductivity mixed powder,
[0111] Modified silicon carbide whiskers 6 parts,
[0112] 25 parts of liquid reactive flame retardant;
[0113] The particle size of the fumed silica is 10 nm;
[0114] The liquid reactive flame retardant is N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester;
[0115] According to the specific formula of component A of the two-component organic silicone adhesive for power battery structure thermal conductivity in parts by weight, α, ω-dihydroxy polydimethylsiloxane, liquid reactive flame retardant and fumed silica are placed in a double planetary mixer, and the vacuum state in the mixer is maintained. The stirring rate is controlled at 110 rpm and the dispersion rate is 8500 rpm. After continuous stirring and dispersion for 4 hours, the modified micro-nano high thermal conductivity mixed powder is added, and stirring and dispersion is continued for 7 hours. The stirring rate is maintained unchanged, and the dispersion rate is reduced to 3500 rpm. Then, the modified silicon carbide whisker is added. After continuous stirring and dispersion for 8 hours, the adhesive solution is obtained. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain the finished product of component A.
[0116] Step 4: Preparation of component B
[0117] The specific formula of the B component is, in parts by weight:
[0118] 10 parts of plasticizing liquid flame retardant,
[0119] 6 parts of tackifier,
[0120] 0.8 parts of catalyst,
[0121] 3 parts of dewatering agent,
[0122] 8 parts of cross-linking agent,
[0123] 4 parts of auxiliary cross-linking agent;
[0124] The plasticizing liquid flame retardant is trioctyl phosphate;
[0125] The tackifier is liquid polycarbosilane;
[0126] The number average molecular weight of the liquid polycarbosilane is 600 g / mol, and the viscosity at room temperature is 200 mPa·s;
[0127] The catalyst is dibutyltin dilaurate;
[0128] The dewatering agent is vinyl trimethoxy silane;
[0129] The cross-linking agent is modified tannic acid;
[0130] The modified tannic acid is prepared by: dissolving tannic acid in acetone, then heating and maintaining the temperature at 50°C, controlling the stirring rate to 300 rpm, adding 3-isocyanate propyltrimethoxysilane under stirring, condensing and reflux, and then stirring and reacting at a constant temperature for 4 hours, and then continuing to maintain the constant temperature, vacuuming and distilling under reduced pressure, and after evacuating and removing the acetone, the obtained solid powder is the modified tannic acid;
[0131] The mass ratio of the tannic acid, acetone and 3-isocyanatepropyltrimethoxysilane is 10:100:3;
[0132] The auxiliary cross-linking agent is diphenylsilanediol;
[0133] According to the specific formula of component B of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, the plasticizer liquid flame retardant, thickener, catalyst, dehydrating agent, cross-linking agent and auxiliary cross-linking agent are placed in a double planetary mixer, and the vacuum state in the mixer is evacuated and maintained. The stirring rate is controlled at 110 rpm and the dispersion rate is 8000 rpm. After stirring and mixing for 6 hours, the adhesive solution is obtained. After vacuum degassing, it is filled into plastic finished product bottles, and sealed with nitrogen to obtain the finished product of component B.
[0134] Example 3: A two-component organic silicone adhesive for heat conduction of power battery structure
[0135] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0136] After the nano aluminum nitride powder and the carbonyl iron powder were placed in a 130° C. oven and dried for 13 hours, they were cooled to room temperature in a dry environment and then added to a high-speed dispersion kettle, followed by the addition of toluene and oleyl linoleate, and after strong dispersion at a speed of 13,000 rpm for 10 hours, the dispersion rate was reduced to 7,000 rpm, silane substances were added, the temperature was raised and kept constant at 90° C., and after constant temperature reaction for 8 hours, the temperature was reduced to room temperature and centrifuged, and the separated solid was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven at 80° C. and dried for 10 hours to obtain a modified micro-nano high thermal conductivity mixed powder;
[0137] The particle size of the nano aluminum nitride powder is 100 nm;
[0138] The particle size of the carbonyl iron powder is 3 μm;
[0139] The silane substance is octamethylcyclotetrasilazane;
[0140] The mass ratio of the nano aluminum nitride powder, carbonyl iron powder, toluene, oleyl linoleate, and silane substances is 20:55:240:10:10.
[0141] Step 2: Preparation of modified silicon carbide whiskers
[0142] The silicon carbide whisker was placed in a 130°C oven and dried for 10 hours, cooled to room temperature in a dry environment, and then added to a high-speed dispersion kettle, followed by adding toluene, and dispersed vigorously at 9000 rpm for 8 hours, then the dispersion rate was reduced to 5000 rpm, 3-aminopropyltrimethoxysilane was added, and the temperature was raised and kept constant at 95°C. After constant temperature reaction for 11 hours, the temperature was reduced to room temperature, filtered, and the filtered solid was washed with anhydrous ethanol for 4 times, and then placed in a 70°C vacuum drying oven and dried for 8 hours to obtain modified silicon carbide whiskers;
[0143] The silicon carbide whisker has a diameter of 0.5 μm and a length of 30 μm;
[0144] The mass ratio of the silicon carbide whisker, toluene and 3-aminopropyltrimethoxysilane is 45:270:9.
[0145] Step 3: Preparation of component A
[0146] The specific formula of the component A is, in parts by weight:
[0147] 160 parts of α,ω-dihydroxy polydimethylsiloxane,
[0148] 2.5 parts of fumed silica,
[0149] 100 parts of modified micro-nano high thermal conductivity mixed powder,
[0150] Modified silicon carbide whiskers 18 parts,
[0151] 45 parts of liquid reactive flame retardant;
[0152] The particle size of the fumed silica is 100 nm;
[0153] The liquid reactive flame retardant is N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester;
[0154] According to the specific formula of component A of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, α, ω-dihydroxy polydimethylsiloxane, liquid reactive flame retardant and fumed silica are put into a double planetary mixer, evacuate and maintain the vacuum state in the mixer, control the stirring rate at 130 rpm and the dispersion rate at 12000 rpm, continue stirring and dispersing for 8 hours, then add the modified micro-nano high thermal conductivity mixed powder, continue stirring and dispersing for 12 hours, maintain the stirring rate unchanged, reduce the dispersion rate to 5000 rpm, then add the modified silicon carbide whisker, continue stirring and dispersing for 11 hours, and obtain the adhesive solution, which is then vacuum degassed and filled into plastic finished product bottles. After nitrogen is filled and sealed, the finished product of component A is obtained.
[0155] Step 4: Preparation of component B
[0156] The specific formula of the B component is, in parts by weight:
[0157] 25 parts of plasticizing liquid flame retardant,
[0158] 15 parts of tackifier,
[0159] 1.3 parts of catalyst,
[0160] 6 parts of dewatering agent,
[0161] 15 parts of cross-linking agent,
[0162] 9 parts of auxiliary cross-linking agent;
[0163] The plasticizing liquid flame retardant is trioctyl phosphate;
[0164] The tackifier is liquid polycarbosilane;
[0165] The number average molecular weight of the liquid polycarbosilane is 900 g / mol, and the viscosity at room temperature is 400 mPa·s;
[0166] The catalyst is dibutyltin dilaurate;
[0167] The dewatering agent is vinyl trimethoxy silane;
[0168] The cross-linking agent is modified tannic acid;
[0169] The modified tannic acid is prepared by: dissolving tannic acid in acetone, then heating and maintaining the temperature at 70°C, controlling the stirring rate to 600 rpm, adding 3-isocyanate propyltrimethoxysilane under stirring, condensing and reflux, and then stirring and reacting at a constant temperature for 9 hours, and then continuing to maintain the constant temperature, vacuuming and distilling under reduced pressure, and after evacuating and removing the acetone, the obtained solid powder is the modified tannic acid;
[0170] The mass ratio of the tannic acid, acetone and 3-isocyanatepropyltrimethoxysilane is 25:250:6;
[0171] The auxiliary cross-linking agent is diphenylsilanediol;
[0172] According to the specific formula of component B of the two-component organic silicone adhesive for heat conduction of power battery structure in parts by weight, the plasticizer liquid flame retardant, thickener, catalyst, dehydrating agent, cross-linking agent and auxiliary cross-linking agent are placed in a double planetary mixer, and the vacuum state in the mixer is maintained. The stirring rate is controlled at 130 rpm and the dispersion rate is 10,000 rpm. After stirring and mixing for 10 hours, the adhesive solution is obtained. After vacuum degassing, it is filled into a plastic finished product bottle, and sealed with nitrogen to obtain the finished product of component B.
[0173] Example 4: A two-component organic silicone adhesive for heat conduction of power battery structure
[0174] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0175] The silane substance is tetramethyldisilazane;
[0176] Other operations are the same as in Example 1;
[0177] The operations of steps 2 and 3 are the same as those of Example 1;
[0178] Step 4: Preparation of component B
[0179] The cross-linking agent is 4,4'-biphenylboronic acid;
[0180] The other operations are the same as those in Example 1.
[0181] Example 5: A two-component organic silicone adhesive for heat conduction of power battery structure
[0182] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0183] The silane substance is hexamethylcyclotrisilazane;
[0184] The other operations are the same as those in Example 1;
[0185] The operations of steps 2, 3 and 4 are the same as those of Example 1.
[0186] Example 6: A two-component organic silicone adhesive for heat conduction of power battery structure
[0187] Step 1: Preparation of modified micro-nano high thermal conductivity mixed powder
[0188] The silane substance is hexamethyldisilazane;
[0189] The other operations are the same as those in Example 1;
[0190] The operations of steps 2, 3 and 4 are the same as those of Example 1.
[0191] Comparative Example 1: Based on Example 1, step 1, preparation of modified micro-nano high thermal conductivity mixed powder, is not performed. In step 3, preparation of component A, 80 parts of modified micro-nano high thermal conductivity mixed powder are replaced by 80 parts of micro-nano high thermal conductivity mixed powder, wherein the mass ratio of nano aluminum nitride powder and carbonyl iron powder contained in the micro-nano high thermal conductivity mixed powder is the same as that in Example 1, and the specific operation is as follows:
[0192] Step 1, preparation of modified micro-nano high thermal conductive mixed powder is not performed;
[0193] The operation of step 2 is the same as that of embodiment 1;
[0194] Step 3: Preparation of component A
[0195] Replace 80 parts of modified micro-nano high thermal conductivity mixed powder with 80 parts of micro-nano high thermal conductivity mixed powder;
[0196] The micro-nano high thermal conductivity mixed powder is composed of nano aluminum nitride powder and carbonyl iron powder, and the mass ratio of nano aluminum nitride powder to carbonyl iron powder is 16:40;
[0197] The other operations are the same as those in Example 1;
[0198] The operation of step 4 is the same as that of embodiment 1.
[0199] Comparative Example 2: Based on Example 1, step 2, preparation of modified silicon carbide whiskers, is not performed. In step 3, preparation of component A, 11 parts of modified silicon carbide whiskers are replaced by 11 parts of silicon carbide whiskers in equal amounts. The specific operations are as follows:
[0200] The operation of step 1 is the same as that of embodiment 1;
[0201] Step 2: Preparation of modified silicon carbide whiskers is not performed
[0202] Step 3: Preparation of component A
[0203] The 11 parts of modified silicon carbide whiskers were replaced by 11 parts of silicon carbide whiskers, and the other operations were the same as in Example 1;
[0204] The operation of step 4 is the same as that of embodiment 1.
[0205] Comparative Example 3: Based on Example 1, in step 3, in the preparation of component A, no liquid reactive flame retardant is added, and 35 parts of liquid reactive flame retardant are replaced by 35 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts. The specific operation is as follows:
[0206] The operations of steps 1 and 2 are the same as those of Example 1;
[0207] Step 3: Preparation of component A
[0208] 35 parts of liquid reactive flame retardant were replaced by 35 parts of α,ω-dihydroxypolydimethylsiloxane, and other operations were the same as in Example 1;
[0209] The operation of step 4 is the same as that of embodiment 1.
[0210] Comparative Example 4: Based on Example 1, in step 4, component B is prepared without adding a tackifier, and 9 parts of the tackifier are replaced by 9 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts. The specific operation is as follows:
[0211] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0212] Step 4: Preparation of component B
[0213] The 9 parts of tackifier were replaced by 9 parts of α,ω-dihydroxypolydimethylsiloxane, and the other operations were the same as in Example 1.
[0214] Comparative Example 5: Based on Example 1, in step 4, component B is prepared without adding a crosslinking agent, and 11 parts of the crosslinking agent are replaced by 11 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts. The specific operation is as follows:
[0215] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0216] Step 4: Preparation of component B
[0217] The 11 parts of cross-linking agent were replaced by 11 parts of α,ω-dihydroxypolydimethylsiloxane, and the other operations were the same as in Example 1.
[0218] Comparative Example 6: Based on Example 4, in step 4, component B is prepared without adding a crosslinking agent, and 11 parts of the crosslinking agent are replaced by 11 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts. The specific operation is as follows:
[0219] The operations of steps 1, 2, and 3 are the same as those of Example 4;
[0220] Step 4: Preparation of component B
[0221] The 11 parts of cross-linking agent were replaced by 11 parts of α,ω-dihydroxypolydimethylsiloxane, and the other operations were the same as those in Example 4.
[0222] Performance Test:
[0223] The two-component organic silicone adhesive for heat conduction of power battery structure obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was mixed evenly with component A and component B in a volume ratio of 1:1 and then glued. The following performance tests were conducted on the gluing process and the obtained glue layer:
[0224] 1. Thermal conductivity: Tested in accordance with ASTM D5470-2012;
[0225] 2. Viscosity of the glue: The rotational viscometer measures the dynamic viscosity of the mixed glue
[0226] 3. Bonding strength: Tested in accordance with GB / T 11211-2009;
[0227] 4. Tensile strength: Tested in accordance with GB / T528-2009;
[0228] 5. Compression modulus: Tested in accordance with GB / T7757-2009;
[0229] 6. Flame retardant performance: tested in accordance with the US ANSI / UL-94-1985 standard;
[0230] The specific test results are shown in Table 1:
[0231] Table 1
[0232]
[0233] From the data in Table 1, it can be seen that in Comparative Example 1, the micro-nano high thermal conductivity mixed powder is not surface modified, the thermal conductivity of Comparative Example 1 is reduced to 1.15W / (m·k), the viscosity of the glue is also increased to 88901mPa·s, the bonding strength is reduced to 2.27MPa, the tensile strength and compression modulus are also reduced to the lowest values in all embodiments and comparative examples, and the flame retardant grade does not change, which shows that the micro-nano high thermal conductivity mixed powder without surface modification is difficult to be uniformly dispersed inside the colloid, which will seriously affect the thermal conductivity of the colloid after curing and the mechanical properties of the cured colloid; Comparative Example 2 in which the silicon carbide whisker is not surface modified is similar to Comparative Example 1, and the performance is only slightly better than Comparative Example 1, which shows that the silicon carbide whisker is not surface modified and is difficult to be uniformly dispersed, so as to affect the thermal conductivity and mechanical properties of the colloid after curing; Comparative Example 3 does not add liquid reactive flame retardant, the thermal conductivity is reduced to 4.32, and the viscosity of the glue is increased to 88952mPa·s , the bonding strength is reduced to 3.08MPa, the tensile strength and compression modulus are also significantly reduced, and the flame retardant grade is reduced to V1, which shows that the liquid reactive flame retardant promotes the dispersion uniformity of the thermal conductive filler and improves the cross-linking degree of the colloid by reducing the viscosity of the glue, thereby affecting the thermal conductivity and mechanical properties of the colloid. In addition, the liquid reactive flame retardant plays a vital role in improving the flame retardant properties of the colloid; in Comparative Example 4, no tackifier is added, the thermal conductivity is reduced, the bonding strength decreases the most, the tensile strength and compression modulus are also significantly reduced, and the flame retardant grade does not change, which shows that the main function of the tackifier is to increase the bonding strength of the colloid, and it can also affect the other mechanical strength and thermal conductivity of the colloid; in Comparative Examples 5 and 6, no cross-linking agent is added, and the situation is similar, the thermal conductivity is significantly reduced, and the mechanical properties are significantly reduced, which shows that the cross-linking agent can affect the thermal conductivity and other mechanical properties of the colloid by increasing the cross-linking density of the colloid after curing.
[0234] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A two-component organic silicone adhesive for heat conduction of power battery structure, characterized in that: The two-component organic silicone adhesive for heat conduction of the power battery structure is composed of component A and component B. When applying the adhesive, component A and component B are evenly mixed in a volume ratio of 5:3-5 and then used; The specific formula of the component A is, in parts by weight: 110-160 parts of α,ω-dihydroxy polydimethylsiloxane, 0.5~2.5 parts of fumed silica, 70~100 parts of modified micro-nano high thermal conductivity mixed powder, Modified silicon carbide whisker 6~18 parts, 25-45 parts of liquid reactive flame retardant; The particle size of the fumed silica is 10-100 nm; The liquid reactive flame retardant is N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid diethyl ester; The specific formula of the B component is, in parts by weight: 10~25 parts of plasticizing liquid flame retardant, Thickener 6~15 parts, Catalyst 0.8~1.3 parts, 3~6 parts of dewatering agent, 8~15 parts of cross-linking agent, 4-9 parts of auxiliary cross-linking agent; The plasticizing liquid flame retardant is trioctyl phosphate; The tackifier is liquid polycarbosilane; The number average molecular weight of the liquid polycarbosilane is 600-900 g / mol, and the viscosity at room temperature is 200-400 mPa·s; The catalyst is dibutyltin dilaurate; The dewatering agent is vinyl trimethoxy silane; The cross-linking agent is one of modified tannic acid and 4,4'-biphenylboronic acid; The modified tannic acid has a preparation method comprising: dissolving tannic acid in acetone, then heating and maintaining the temperature at 50-70°C, controlling the stirring rate at 300-600 rpm, adding 3-isocyanate propyltrimethoxysilane under stirring, condensing and reflux, and then reacting at a constant temperature for 4-9 hours, continuing to maintain the constant temperature, performing vacuum distillation, and removing the acetone to obtain a solid powder, which is the modified tannic acid; The mass ratio of the tannic acid, acetone and 3-isocyanate propyltrimethoxysilane is 10-25:100-250:3-6; The auxiliary cross-linking agent is diphenylsilanediol; The modified micro-nano high thermal conductivity mixed powder is prepared by: placing nano aluminum nitride powder and carbonyl iron powder in an oven at 100-130° C. for 9-13 hours, cooling to room temperature in a dry environment, and then adding them to a high-speed dispersion kettle, then adding toluene and oleyl linoleate, and strongly dispersing at a speed of 8000-13000 rpm for 6-10 hours, reducing the dispersion rate to 4000-7000 rpm, adding silane substances, heating and maintaining a constant temperature of 60-90° C., reacting at a constant temperature for 4-8 hours, reducing the temperature to room temperature, centrifuging, washing the separated solid with anhydrous ethanol for 3-5 times, and drying it in a vacuum drying oven at 50-80° C. for 6-10 hours to obtain the modified micro-nano high thermal conductivity mixed powder; The silane substance is one of hexamethyldisilazane, hexaethyldisilazane, octamethylcyclotetrasilazane, tetramethyldisilazane, hexamethylcyclotrisilazane and hexamethyldisilazane; The mass ratio of the nano aluminum nitride powder, carbonyl iron powder, toluene, oleyl linoleate, and silane substances is 10-20:30-55:160-240:3-10:5-10; The particle size of the nano aluminum nitride powder is 10-100 nm; The particle size of the carbonyl iron powder is 0.5-3 μm; The modified silicon carbide whisker has a preparation method comprising: placing the silicon carbide whisker in a 100-130°C oven and drying it for 5-10 hours, cooling it to room temperature in a dry environment, and then adding it to a high-speed dispersion kettle, then adding toluene, and strongly dispersing it at a speed of 6000-9000 rpm for 5-8 hours, then reducing the dispersion rate to 2000-5000 rpm, adding 3-aminopropyltrimethoxysilane, raising the temperature and keeping the temperature constant at 70-95°C, reacting at the constant temperature for 6-11 hours, then reducing the temperature to room temperature, filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and then placing it in a 40-70°C vacuum drying oven and drying it for 4-8 hours to obtain the modified silicon carbide whisker; The silicon carbide whisker has a diameter of 0.1-0.5 μm and a length of 10-30 μm; The mass ratio of the silicon carbide whisker, toluene and 3-aminopropyltrimethoxysilane is 15-45:150-270:4-9.
2. The two-component organic silicone adhesive for heat conduction of power battery structure according to claim 1, characterized in that: The preparation method of the component A is as follows: according to the specific formula of the two-component organic silicone adhesive component A for power battery structure heat conduction in parts by weight, α, ω-dihydroxy polydimethylsiloxane, liquid reactive flame retardant, and fumed silica are placed in a double planetary mixer, vacuuming and maintaining the vacuum state in the mixer, controlling the stirring rate to 110-130 rpm and the dispersion rate to 8500-12000 rpm, continuously stirring and dispersing for 4-8 hours, then adding the modified micro-nano high thermal conductivity mixed powder, continuing to stir and disperse for 7-12 hours, maintaining the stirring rate unchanged, reducing the dispersion rate to 3500-5000 rpm, then adding the modified silicon carbide whisker, continuously stirring and dispersing for 8-11 hours, obtaining the adhesive solution, and then vacuum degassing, filling it into a plastic finished product bottle, and sealing it with nitrogen to obtain the component A finished product.
3. The two-component organic silicone adhesive for heat conduction of power battery structure according to claim 1, characterized in that: The preparation method of the component B is as follows: according to the specific formula of the two-component organic silicone adhesive component B for heat conduction of power battery structure in parts by weight, a plasticizing liquid flame retardant, a tackifier, a catalyst, a dehydrating agent, a cross-linking agent, and a cross-linking aid are placed in a double planetary mixer, vacuuming and maintaining the vacuum state in the mixer, controlling the stirring rate to 110-130 rpm and the dispersion rate to 8000-10000 rpm, stirring and mixing for 6-10 hours to obtain a glue solution, and then after vacuum degassing, filling it into a plastic finished product bottle, filling it with nitrogen and sealing it, to obtain a finished product of component B.
Citation Information
Patent Citations
Low-specific-gravity flame-retardant heat-conducting pouring sealant for automobile power battery and preparation method thereof
CN106867444A
High-temperature-resistant flame-retardant organic silicon pouring sealant and preparation method thereof
CN112940674A
Pouring sealant as well as preparation method and application thereof
CN113150739A
High-thermal-conductivity self-leveling modified ceramic liquid potting material and preparation method therefor
WO2022057083A1